HAKIM AGUNG DAN PEMBAHARU HUKUM MENUJU PENGADILAN YANG BERSIH - Ibnu Artadi (Fakultas Hukum, Universitas Islam Bandung, 2011)
Jurisprudence product of Judge (Supreme) was born from the process of law discovery. It has concrete nature in contact with reality and justice as well as implications for law reformers. The intensity of supervision with the law advantage has effort to achieve the same perception of justice, and also as the one of tools to control whether there are any malpractices or not toward the realization of truthful judiciary.